PERANCANGAN MOBILE E-COMMERCE PRODUK DESA DAN HASIL BUMI DI KECAMATAN PINOLAGUMAN KABUPATEN BOLAANG MONGONDOW UTARA - Zainudin Sidik; Marlin Lasena (JSAI (Journal Scientific and Applied Informatics), 2022)
At present the process of selling and marketing village products is still carried out conventionally, namely by selling it to collectors, so that the benefits they get are few. Along with the development of increasingly advanced information technology, it is realized the need to improve information technology services. At present the community needs information system services that are expected to help in the process of selling and marketing agricultural products, namely by creating e-commerce applications for village products and android-based agricultural products. which helps the community in the process of selling and marketing without going through collectors so that the benefits they get are more leverage. Considering that currently it is also still in a Pandemic Covid condition 19 The results of the implementation of this research are made very simple in order to make it easier for the community to manage applications and the results of the system testing both WhiteBox and Blackbox get the results that are in accordance with the display design expected by the user